In Vivo Tau Imaging for a Diagnostic Platform of Tauopathy Using the rTg4510 Mouse Line - Sahara, Naruhiko; Shimojo, Masafumi; Ono, Maiko; Takuwa, Hiroyuki; Febo, Marcelo; Higuchi, Makoto; Suhara, Tetsuya (Frontiers in Neurology, 2017)
Association of tau deposition with neurodegeneration in Alzheimer’s disease (AD) and related tau-positive neurological disorders collectively referred to as tauopathies indicates contribution of tau aggregates to neurotoxicity. The discovery of tau gene mutations in FTDP-17-tau kindreds has provided unequivocal evidence that tau abnormalities alone can induce neurodegenerative disorders. Therefore, visualization of tau accumulation would offer a reliable, objective index to aid in the diagnosis of tauopathy and to assess the disease progression. Positron emission tomography (PET) imaging of tau lesions is currently available using several tau PET ligands. Because most tau PET ligands have the property of an extrinsic fluorescent dye, these ligands are considered to be useful for both PET and fluorescence imaging. In addition, small-animal magnetic resonance imaging (MRI) is available for both structural and functional imaging. Using these advanced imaging techniques, in vivo studies on a mouse model of tauopathy will provide significant insight into the translational research of neurodegenerative diseases. In this review, we will discuss the utilities of PET, MRI and fluorescence imaging for evaluating the disease progression of tauopathy.